긴급치료격리병동의 평면유형 - 이현진; 권순정 (의료·복지 건축, 2022)
Purpose: In response to the rapid spread of COVID-19 in 2020, the government supported facilities and equipment through the ‘Urgent Isolation Ward Expansion Project’. Design and remodeling of efficient negative pressure isolation facilities had to be done in a short period of time, and the performance gap between facilities was very large because the types of hospitals and wards of existing medical facilities were diverse. In order to secure the stability of isolation wards between medical facilities and reduce the facility gap, guidelines for planning isolation wards considering the diversity of each hospital should be appropriately presented. In consideration of these points, this study aims to provide basic data for future remodeling guidelines for each plan type of the negative pressure isolation ward first. Methods: We analyzed the plans before and after the change of 13 case hospitals that performed the urgent care bed expansion project for COVID-19 confirmed patients. Before the remodeling, the current status of the facility was analyzed according to the type of corridor, the location of the nursing station, and the location of the elevator. After remodeling, the flow of medical staff and patients, the flow of entry and exit of clean and contaminated items, and the space of negative pressure and non-negative pressure areas. Results: The ward type was divided into three types according to the corridor type and room arrangement: double loaded corridor type with two side wards, race track type with one side ward, and race track type with two side wards. Based on these three types, the standard floor plan type of the isolation ward was proposed in terms of the location of the elevator bank and Nurse station. Implications: When the existing general ward is converted into a negative pressure isolation ward, this study can be a basic data to present customized guidelines for each ward type.
Keywords: 긴급치료격리병동; 평면유형; 음압병실; Urgent Isolation Ward; Health Care Facility; Ward types; Negative Pressure Bedroom